Epigenetic and Transcriptional Regulation of Spontaneous and Sensory Activity Dependent Programs During Neuronal Circuit Development - Pumo, Gabriele M.; Kitazawa, Taro; Rijli, Filippo M. (Frontiers in Neural Circuits, 2022)
Spontaneous activity generated before the onset of sensory transduction has a key role in wiring developing sensory circuits. From axonal targeting, to synapse formation and elimination, to the balanced integration of neurons into developing circuits, this type of activity is implicated in a variety of cellular processes. However, little is known about its molecular mechanisms of action, especially at the level of genome regulation. Conversely, sensory experience-dependent activity implements well-characterized transcriptional and epigenetic chromatin programs that underlie heterogenous but specific genomic responses that shape both postnatal circuit development and neuroplasticity in the adult. In this review, we focus on our knowledge of the developmental processes regulated by spontaneous activity and the underlying transcriptional mechanisms. We also review novel findings on how chromatin regulates the specificity and developmental induction of the experience-dependent program, and speculate their relevance for our understanding of how spontaneous activity may act at the genomic level to instruct circuit assembly and prepare developing neurons for sensory-dependent connectivity refinement and processing.